Grammar Practice Activities : A Practical Guide for Teachers - Ur P. (Cambridge Cambridge University Press, 1998)
For the teacher who wishes to combine grammar teaching with a broadly communicative methodology, this is an invaluable resource. It contains a collection of imaginative and interesting grammar practice activities suitable for a wide range of levels and ages. Part one provides: * a detailed introduction to grammar teaching * guidelines for the design of activities * practical hints on effective classroom presentation. Part two contains: * almost 200 game-like activities for practising important or problematical aspects of English grammar, with detailed descriptions of procedure * sample texts and visuals which may be photocopied for immediate use.
Keywords: 811.111